The Effect of Breeds on Physical and Chemical Quality of Meat - Djalal Rosyidi; Agus Susilo; Ivan Wiretno (Faculty of Animal Science Universitas Brawijaya, 2010)
This research was carried out in slaughtering house at Krian Sidoarjo, Laboratory of Airlangga University and Laboratory of Animal Product Technology, Animal Husbandry Faculty, Brawijaya University ofÂ Malang. The material used in the research were PO cow and inbreeding Limosin with PO. This present work aimed to know the physical and chemical composition of meats of PO cow and inbreeding Limosin with PO. Independent t test was used in the experiment. Evaluated variables were physical quality including: Water Holding Capacity (WHC), tenderness and chemical quality including pH, water moisture, protein content and fat content.The result showed that the difference effect of breeds on physical quality and chemical quality did not give significant effect. Â Keywords : Breeds, Physical and Chemical Quality